Faculty Development Handbook:An Effective Performance Enhancement Tool for Instructors - Shukla, Somendra; Gupta, Manish; Jindal, Neerja; Sidana, Shubham (Journal of Engineering Education Transformations, 2025)
Maintaining the quality every time in any field is a big challenge and engineering education is not an exception. Due to various limitations and constraints, the quality of teaching and in result learning suffers. The delivery of lectures of every instructor varies due to these limitations. This paper proposes a handbook based approach so that the teachers follow a common agenda throughout the course without losing the essential freedom in teaching a course. Handbook is also useful in maintaining the record of the continuous improvement in teaching skills. The results have proved that alignment of teaching efforts through a well designed handbook helps in making a better teaching learning environment.